TNIP1 reduction of HSPA6 gene expression occurs in promoter regions lacking binding sites for known TNIP1-repressed transcription factors - Ramirez, Vincent P. (Gene, 2014)
TNFα-induced protein 3-interacting protein 1 (TNIP1) represses signaling pathways initiated by specific nuclear and transmembrane receptors. This effect results in reduced activity of distinct transcription factors such as retinoic acid receptors (RAR), peroxisome-proliferator-activated receptors (PPAR), and NFκB. TNIP1-null and TNIP1-knockin defective for ubiquitin-binding mice show increased liver apoptosis, and enlarged spleen and lymph nodes, respectively. To complement current knowledge of TNIP1’s broad physiologic functions as interpreted from in vivo studies and specific expression consequences from transcription factor repression, we determined effects of excess TNIP1 on global gene regulation. Following experimentally increased expression of TNIP1 in cultured keratinocytes, our gene expression microarray analysis not only confirmed TNIP1’s association in previously known pathways and functions but also found a novel TNIP1-regulated pathway – the cell stress response. Under standard culture conditions, expression of several heat shock proteins, including HSPA1A, HSPA6, DNAJA1 and DNAJB1, was reduced. In heat-stressed conditions, differential regulation of HSPA1A and HSPA6 was observed, where only HSPA6 expression was reduced after heat-shock. Using HSPA6 as a model to elucidate the mechanism of the TNIP1-mediated HSP repression, we determined TNIP1 likely represses HSPs through factors other than RAR, PPAR or NFκB despite presence of these factors’ binding sites in the HSPA6 promoter. These results indicate that regulation of HSPs may be through a yet unknown TNIP1-associated pathway. Additionally, these results suggest TNIP1’s reduction of HSP expression levels could negatively impact HSP chaperone capacity or their participation in the cell stress response.